Controlling hot electrons via plasmon coupling to enhance catalytic reactions in plasmonic Au@SiO2-Pt structures - Yuan, Xu (Nanyang Technological University, 2022)
Recently, photocatalysis utilizing the localized surface plasmon resonance (LSPR) of plasmonic metal materials has drawn significant interest. Localized surface plasmon can decay non-radiatively by excitation of hot electrons. Meanwhile, the oscillation of surface plasmon can generate an enhanced local electric field confined to the surface of plasmonic nanoparticles. Plasmon-induced hot electrons and enhanced local electric field are crucial in many photochemical applications. However, the mutual interaction between hot electrons and enhanced local electric field is still elusive. Therefore, this thesis aims to investigate the behavior of hot electrons under strong local electric field and design rational strategy to enhance catalytic ability of plasmonic photocatalyst.